Aktivitas Antibakteri Kombinasi Minyak Atsiri Daun Kemangi (Ocimum Basilicum L.) dan Daun Jeruk Purut (Citrus Hystrix D.C.) terhadap Escherichia Coli ATCC 25922 - Fitri Jati Rukmana; Reslely Harjanti; Dyonisius Andang Arif Wibawa (Fakultas Ilmu Kesehatan Universitas Setia Budi Surakarta, 2019)
Basil essential oil has a component of linalool compounds belonging to terpenoid derivatives which have an antibacterial effect and essential oils of kaffir lime have citronella compounds which can inhibit the growth of various types of bacteria. This study aims to determine the antibacterial activity of essential oils of basil leaves, kaffir lime leaves and the combination of both against Escherichia coli bacteria ATCC 25922. This study has used diffusion methods to test antibacterial activity. The concentration of the sample was 2% and 4% with a ratio combination of essential oils were 1:1; 1: 2; 2:1. Then the research data were analyzed with two way Analysis of Variance (ANOVA). The results showed that essential oils in the combination of basil leaves (Ocimum basilicum L.) and kaffir lime leaves (Citrus hystrix D.C) had antibacterial activity against Escherichia coli ATCC 25922 with concentrations of 2% and 4%. Variations of essential oils from basil (Ocimum basilicum L.) leaves and kaffir lime (Citrus hystrix D.C) leaves with a ratio of 1:2 at a concentration of 4% has the greatest inhibitory potential against Escherichia coli ATCC 25922 with inhibition diameters of 15.5 mm.